A Novel No Foil-to-Skin Contact Technique for Vacuum-assisted Wound Closure in Patients with Sensitive Skin - Iliyan Emilov Iliev, MD; Anna-Maria Koutny-Adensamer, MD; Friedrich Herbst, MD; Bernhard Dauser, MD (Plastic and Reconstructive Surgery, Global Open, 2023)
Background:. In some patients with chronic wounds, the surrounding skin is so injured due to various underlying conditions that negative pressure dressing cannot be applied or cannot function properly. Having faced this problem in our everyday practice, we developed a new skin-sparing technique for vacuum-assisted wound closure, which ensures that the peri-wound skin does not come into contact with the transparent adhesive films. Methods:. For 9 months (April–December 2022), we performed 32 vacuum wound dressings with the newly developed technique using the 3M ActiV.A.C. Therapy Unit and accessories, and Convatec’s VARIHESIVE, avoiding skin contact with the adhesive films. Results:. Seven patients with 11 wounds who had sensitive skin or allergy to the conventionally used adhesive films were successfully treated with the new technique. The negative pressure wound dressings remained intact and functioned properly for up to 168 hours without compromising patients’ daily activities and therapy. Conclusion:. The novel “no foil-to-skin contact” technique for vacuum-assisted wound closure can successfully be incorporated in the treatment of patients in whom conventional negative pressure dressings are otherwise not applicable.